Pengetahuan tenaga kesehatan gigi dan mulut di puskesmas terhadap teledentistry pada masa adaptasi kebiasaan baru (kajian pada tenaga kesehatan gigi dan mulut di puskesmas kota balikpapan) - Sadina Aulia; Marta Juslily (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Teledentistry is an alternative service using the application of information and telecommunications technology combined with dentistry through long-distance communication media. Teledentistry is nothing new in dentistry, but teledentistry is becoming more popular due to the COVID-19 pandemic. The government through the Ministry of Health of the Republic of Indonesia issued an appeal letter during the new normal period for teledentistry to be used, especially in public health center. Teledentistry is useful for screening pre-visit patients, selecting cases according to the priority scale of the need for treatment and the level of risk of exposure to COVID-19 infection to staff, as well as providing referrals and drug prescriptions if necessary. The Ministry of Health of the Republic of Indonesia has issued Technical Guidelines for Dental and Oral Medical Staff at First Level Health Facilities during the New Normal Period. Purpose: To find out the description of the knowledge of dental and oral medical staff towards teledentistry at the Balikpapan City public health center during the new normal period. Researceh Methods: Descriptive observation with a cross-sectional study design on the description of the knowledge of dental and oral medical staff towards teledentistry during the new normal period at the Balikpapan City public health center. Measurement of the level of knowledge using a questionnaire designed with a total of 13 statements. Result: The majority of dental and oral medical staff at the Balikpapan City public health center have good knowledge of teledentistry, as many as 90% of respondents. This is supported by the majority of respondents, as many as 71.7% of respondents have used teledentistry. Meanwhile, as many as 10% of respondents had sufficient knowledge and there were no respondents who had insufficient knowledge of teledentistry. Conclusion: Based on research that has been done on 60 dental and oral medical staff in 27 Balikpapan City public health center, the results represent that 90% (54) of respondents have good knowledge of teledentistry.